Binder-free graphene electrode material and preparation method and application thereof
Through the preparation method of graphene electrode material without binder, the green one-step hydrothermal reaction technology is used to solve the performance reduction problem caused by adhesives in traditional graphene electrode materials, and the efficient electrochemical performance and environmentally friendly preparation process is achieved.
Patent Information
- Application Number
- CN202510323502.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-05-30
AI Technical Summary
The use of adhesives and conductive agents is required during the preparation of existing graphene electrode materials, which leads to a decrease in the effective specific surface area of the electrode material, affecting its electrochemical performance, and the adhesive may react sideways during the charge and discharge process, reducing the stability of the electrode material.
Using the method of preparing graphene electrode material without binder, self-supported graphene electrode material is obtained by dissolving graphene ink in deionized water, mixing it with Fenton reagent, and carrying out a green one-step hydrothermal reaction and loading it on a conductive substrate.
It significantly improves the accessibility of active sites, realizes efficient transmission of electrolyte ions and electron transfer, has a high area-specific capacitance and excellent electrochemical performance, avoids the use of strong acids, and reduces the burden on the environment.
Smart Images

Figure CN120072531A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of electrode materials, and specifically relates to a binder-free graphene electrode material, a preparation method thereof, and an application thereof. Background Art
[0002] With the development of society, the global demand for energy is increasing day by day. Energy has a profound impact on our living standards and the development of social economy. Stable energy supply is a key factor for the success of modern society. The rapid development of research in this field is precisely to meet the urgent needs of society for new, low-cost, environmentally friendly, and highly efficient energy conversion and energy storage, so as to adapt to the development of modern society and at the same time solve the increasingly severe environmental problems.
[0003] At present, for various energy storage materials and methods, researchers have carried out a large number of studies. As an energy storage technology, supercapacitors (SCs) are an effective alternative to battery energy storage. Different from batteries, supercapacitors (SCs) do not need to be charged before use and can handle higher power levels, with higher efficiency than batteries. Nowadays, most advanced rechargeable energy storage industries are committed to designing and manufacturing electrochemical energy storage systems with high adaptability, high energy and power density, and low unit storage capacity cost. Traditional batteries are mostly based on lithium-ion batteries (LIBs). Based on the above advantages, supercapacitors (SCs) are regarded as potential alternative choices for conventional LIBs. In addition, there are many limiting factors for batteries. For example, in cold ambient temperatures or when the charge-discharge cycles are short, the output of the battery will drop significantly. Moreover, the management cost of the battery is high and its service life is limited. Generally speaking, the electrochemical performance of supercapacitors (SCs) depends to a large extent on the performance of the electrode materials. Among many electrode materials, activated carbon (AC), carbon nanotubes, and graphene materials, as typical carbon materials, have received extensive attention and in-depth research from many researchers and are often used as electrode materials for SCs. Among various carbon materials, graphene materials are particularly remarkable. First, graphene materials have excellent electron mobility, which can greatly promote the propagation of electrons during the charging and discharging processes, thereby significantly improving the electrochemical performance of SCs. Second, from a theoretical perspective, the specific surface area (SSA) of the electric double layer capacitance of graphene materials is large and the theoretical value is quite high, which means it has great potential in the field of SCs. At the same time, its raw material graphite has rich reserves and can be prepared on a large scale at a low cost. Moreover, graphene materials also have excellent mechanical stability, chemical stability, and thermal stability, which provide reliable guarantees for the long-term stable operation of the SCs energy storage system. However, the carbon materials currently used are usually in powder form and need to be mixed with binders and conductive agents in a certain proportion and then coated on the current collector to prepare supercapacitor electrodes. However, the addition of binders and conductive agents may change the pore structure of the electrode materials, resulting in a decrease in the effective specific surface area of the electrode materials and affecting their electrochemical performance. In addition, side reactions that may occur during the charge-discharge process of the binder will lead to a decrease in the stability of the electrode materials. Therefore, the present invention proposes a binder-free graphene electrode material, its preparation method and application to solve the problems existing in the prior art. Summary of the Invention
[0004] The purpose of the present invention is to provide a binder-free graphene electrode material, its preparation method and application to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: A binder-free graphene electrode material, comprising a conductive substrate and a graphene material, wherein the graphene material is loaded on the conductive substrate through a green one-step hydrothermal reaction.
[0006] Preferably, the conductive substrate is one of nickel foam, carbon cloth or carbon paper.
[0007] A preparation method of a binder-free graphene electrode material, comprising the following steps:
[0008] Step 1: First, dissolve the graphene ink in deionized water for dilution, stir evenly and ultrasonicate to obtain a uniformly dispersed dilution;
[0009] Step 2: Add the Fenton reagent to the dilution obtained in Step 1 to obtain a mixed solution;
[0010] Step 3: Then place the pre-prepared conductive substrate into the mixed solution obtained in Step 2 for hydrothermal reaction, and then wash and dry to obtain a self-supporting graphene electrode material.
[0011] Preferably, the Fenton reagent source in Step 2 is selected from one or more of ferric chloride, ferric sulfate, and ferric nitrate.
[0012] Preferably, the content of iron ions in the Fenton reagent in Step 2 is 0.01% - 0.1% (wt), and the volume of hydrogen peroxide is 5 - 15 mL.
[0013] Preferably, the temperature of the hydrothermal reaction in Step 3 is set to 140 - 200 °C, and the time is set to 6 - 12 h.
[0014] Preferably, the reaction product obtained after the hydrothermal reaction of the mixed solution on the surface of the conductive substrate is sequentially washed, dried and cooled.
[0015] Preferably, the reaction product is washed with deionized water or ethanol, and the reaction product is dried by vacuum drying after washing, with the drying temperature set to 40 - 70 °C and the drying time set to 6 - 12 h.
[0016] An application of a binder-free graphene electrode material, wherein the graphene material is used as a working electrode in a supercapacitor.
[0017] The beneficial effects of the present invention are as follows:
[0018] By utilizing the Fenton reaction to synthesize a binder-free graphene electrode material, it not only effectively avoids the use of strong acids in the traditional preparation process, greatly reduces the environmental burden, embodies the concept of green chemistry, but also dilutes the graphene ink by dissolving it in deionized water, then mixes it with the Fenton reagent, conducts a hydrothermal reaction on the surface of the conductive substrate, and then washes and dries it to obtain a self-supporting graphene electrode material. The obtained graphene electrode material can significantly improve the accessibility of active sites, thereby realizing the efficient transport of electrolyte ions and promoting the transfer of electrons in the electrode. It has a high areal capacitance, excellent electrochemical performance, and shows broad application prospects, providing strong support for promoting the development of new energy technologies and electrochemical technologies. Brief Description of the Drawings
[0019] Figure 1 is the scanning electron microscope scan of the electrode material prepared in Example 1 of the present invention;
[0020] Figure 2 is the scanning electron microscope scan of the electrode material prepared in Example 2 of the present invention;
[0021] Figure 3 is the scanning electron microscope scan of the electrode material prepared in Example 3 of the present invention;
[0022] Figure 4 is the X-ray diffraction pattern of the electrode materials prepared in Examples 1 to 3 of the present invention;
[0023] Figure 5 is the Raman spectrum of the electrode materials prepared in Examples 1 to 3 of the present invention;
[0024] Figure 6 is the cyclic voltammogram of the electrode material prepared in Example 1 of the present invention in 6 mol / L KOH solution;
[0025] Figure 7 is the galvanostatic charge-discharge graph of the electrode material prepared in Example 1 of the present invention in 6 mol / L KOH solution;
[0026] Figure 8 is the cyclic voltammogram of the electrode material prepared in Example 2 of the present invention in 6 mol / L KOH solution;
[0027] Figure 9 is the galvanostatic charge-discharge graph of the electrode material prepared in Example 2 of the present invention in 6 mol / L KOH solution;
[0028] Figure 10 is the cyclic voltammogram of the electrode material prepared in Example 3 of the present invention in 6 mol / L KOH solution;
[0029] Figure 11 It is the constant current charge-discharge diagram of the electrode material prepared in Example 3 of the present invention in 6 mol / L KOH solution. Specific embodiments
[0030] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0031] Example 1
[0032] As Figure 1 、 Figures 4 to 7 shown, the embodiment of the present invention provides a binder-free graphene electrode material, including a conductive substrate and graphene material, and the graphene material is loaded on the conductive substrate through a green one-step hydrothermal reaction.
[0033] Graphene has an extremely high electron mobility and excellent electrical conductivity. Loading it on the conductive substrate can further enhance the electrical conductivity of the entire system.
[0034] Among them, the conductive substrate is one of nickel foam, carbon cloth or carbon paper.
[0035] By selecting nickel foam, carbon cloth or carbon paper as the conductive substrate, the electrochemical performance of the composite material can be significantly improved after combination with graphene.
[0036] A preparation method of a binder-free graphene electrode material includes the following steps:
[0037] Step 1: First, dissolve graphene ink in deionized water for dilution, dilute the ink 8 times, stir evenly and ultrasonicate. The stirring time is 0.5 hours, and the ultrasonication time is 0.5 hours to obtain a uniformly dispersed dilution;
[0038] Step 2: Select ferric chloride as the iron source in the Fenton reagent, and add the Fenton reagent to the dilution obtained in Step 1 to obtain a mixed solution;
[0039] Step 3: Prepare the pre-treated nickel foam as a conductive substrate in advance, then vertically fix the conductive substrate at the bottom of a polytetrafluoroethylene-lined reaction kettle. Next, pour the mixed solution obtained in Step 2 into the reaction kettle, and carry out a hydrothermal reaction of the mixed solution on the surface of the conductive substrate in a constant-temperature hydrothermal oven. The temperature of the hydrothermal reaction is 140 °C, and the time of the hydrothermal reaction is 8 h. After the hydrothermal reaction, first wash the obtained reaction product successively with deionized water and absolute ethanol, and then dry the reaction product by vacuum drying. The drying temperature is 60 °C, and the drying time is 6 h. After drying, cool the reaction product to room temperature to obtain a binder-free graphene electrode material;
[0040] The pre-treatment steps of the nickel foam are as follows: First, cut the nickel foam into nickel foam blocks with a size of 1×1×2 cm, then ultrasonically clean the nickel foam blocks successively with absolute ethanol and deionized water for 15 min. After cleaning, dry them in a vacuum oven at a drying temperature of 60 °C for 6 h to obtain the pre-treated nickel foam.
[0041] Use the prepared graphene electrode as the working electrode, a platinum sheet as the counter electrode, Hg / HgO as the reference electrode, and 6 mol / L KOH solution as the electrolyte to form a three-electrode system. Use a Shanghai Chenhua electrochemical workstation (CHI 760E) to perform cyclic voltammetry tests and constant current charge-discharge tests on the prepared graphene electrode material. The obtained cyclic voltammogram is as shown in the accompanying drawings of the specification Figure 6 as shown, and the constant current charge-discharge curve is as shown in the accompanying drawings of the specification Figure 7 as shown. It is calculated that when the current density is 2 mA / cm 2 , the specific area capacitance of the obtained electrode material is 1087.13 mF / cm 2 . By dissolving the graphene ink in deionized water for dilution, and through stirring and ultrasonic treatment, a uniformly dispersed graphene dilution can be obtained, improving the dispersibility of graphene in the solution, providing a uniform reaction environment for subsequent reactions. Finally, the prepared self-supporting graphene electrode material has excellent conductivity and does not use strong acids, playing a role in protecting the environment and having broad application prospects in batteries and supercapacitors.
[0042] Among them, the Fenton reagent source in Step 2 is selected from one or more of ferric chloride, ferric sulfate, and ferric nitrate.
[0043] By using ferric chloride, ferric sulfate, and ferric nitrate as the Fenton reagent, the preparation cost is reduced, making the product more economical and practical.
[0044] Among them, the content of iron ions in the Fenton reagent in Step 2 is 0.01% - 0.1% (wt), and the volume of hydrogen peroxide is 5 - 15 mL.
[0045] By strictly controlling the content of iron ions in the Fenton reagent and the volume of hydrogen peroxide, the performance of the prepared product is made more excellent.
[0046] Among them, in step three, the temperature of the hydrothermal reaction is set to 140 - 200 °C, and the time is set to 6 - 12 h.
[0047] By controlling the temperature and time of the hydrothermal reaction, a graphene electrode material with higher conductivity is prepared, improving the stability of the electrode material during the electrochemical cycling process.
[0048] Among them, after the hydrothermal reaction of the mixed solution on the surface of the conductive substrate in step three, the obtained reaction product is successively washed, dried, and cooled.
[0049] By washing and drying the reaction product, the morphology and structure of the reaction product can be controlled. Washing can remove excess liquid and unfixed substances, while drying can make the reaction product form a stable solid form, which is beneficial for subsequent processing and application.
[0050] Among them, the reaction product is washed with deionized water or ethanol, and after washing, the reaction product is dried by vacuum drying. The drying temperature is set to 40 - 70 °C, and the drying time is 6 - 12 h.
[0051] By controlling the drying temperature, it is possible to avoid incomplete drying of the reaction product due to too low temperature, and at the same time avoid structural changes or performance loss of the reaction product due to too high temperature. At the same time, the control of the drying time ensures that the product can be fully dried.
[0052] An application of a binder-free graphene electrode material, where the graphene material is used as a working electrode in a supercapacitor.
[0053] The prepared graphene material has a high specific capacitance per unit area and good electrochemical performance. As a working electrode applied to a supercapacitor, it has good application prospects.
[0054] Example Two
[0055] As Figure 2 、 Figure 4 、 Figure 5 、 Figure 8 and Figure 9 shown, the embodiment of the present invention provides a binder-free graphene electrode material, including a conductive substrate and a graphene material. The graphene material is loaded on the conductive substrate through a green one-step hydrothermal reaction.
[0056] Graphene has an extremely high electron mobility and excellent electrical conductivity. Loading it on the conductive substrate can further enhance the electrical conductivity of the entire system.
[0057] Among them, the conductive substrate is one of nickel foam, carbon cloth or carbon paper.
[0058] By selecting nickel foam, carbon cloth or carbon paper as the conductive substrate, the electrochemical performance of the composite material can be significantly improved after combination with graphene.
[0059] A preparation method of a binder-free graphene electrode material includes the following steps:
[0060] Step 1: First, dissolve graphene ink in deionized water for dilution, dilute the ink 8 times, stir evenly and then sonicate. The stirring time is 0.5 hours and the sonication time is 0.5 hours to obtain a uniformly dispersed dilution.
[0061] Step 2: Select ferric chloride as the iron source in the Fenton reagent, and add the Fenton reagent to the dilution obtained in Step 1 to obtain a mixed solution.
[0062] Step 3: Prepare the pretreated nickel foam as the conductive substrate in advance, then vertically fix the conductive substrate at the bottom of the polytetrafluoroethylene-lined reaction kettle, and then pour the mixed solution obtained in Step 2 into the reaction kettle. Perform a hydrothermal reaction on the surface of the conductive substrate in a constant temperature water bath. The temperature of the hydrothermal reaction is 160 °C and the hydrothermal reaction time is 8 h. After the hydrothermal reaction, first wash the obtained reaction product with deionized water and anhydrous ethanol in sequence. After the washing is completed, dry the reaction product by vacuum drying. The drying temperature is 60 °C and the drying time is 6 h. After drying is completed, cool the reaction product to room temperature to obtain the binder-free graphene electrode material.
[0063] The pretreatment steps of nickel foam are as follows: First, cut the nickel foam into nickel foam blocks with a size of 1×1×2 cm, then ultrasonically clean the nickel foam blocks with anhydrous ethanol and deionized water in sequence. The cleaning time is 15 min. After the cleaning is completed, perform drying treatment in a vacuum oven. The drying temperature is 60 °C and the drying time is 6 h to obtain the pretreated nickel foam.
[0064] Use the prepared graphene electrode as the working electrode, a platinum sheet as the counter electrode, Hg / HgO as the reference electrode, and 6 mol / L KOH solution as the electrolyte to form a three-electrode system. Use a Shanghai Chenhua electrochemical workstation (CHI 760E) to perform cyclic voltammetry tests and constant current charge-discharge tests on the prepared graphene electrode material. The obtained cyclic voltammogram is as shown in the accompanying drawings of the specification Figure 8 as shown, and the constant current charge-discharge curve is as shown in the accompanying drawings of the specification Figure 9 as shown. Calculate that at a current density of 2 mA / cm 2 ², the specific area capacitance of the obtained electrode material is 4933.19 mF / cm 2, by dissolving the graphene ink in deionized water for dilution and through stirring and ultrasonic treatment, a uniformly dispersed graphene diluent can be obtained, improving the dispersion of graphene in the solution and providing a uniform reaction environment for subsequent reactions. Finally, the prepared self-supporting graphene electrode material has excellent conductivity and does not use strong acids, playing a role in environmental protection and having broad application prospects in batteries and supercapacitors.
[0065] Among them, the Fenton reagent source in step two is selected from one or more of ferric chloride, ferric sulfate, and ferric nitrate.
[0066] By using ferric chloride, ferric sulfate, and ferric nitrate as the Fenton reagent, the preparation cost is reduced, making the product more economical and practical.
[0067] Among them, the content of iron ions in the Fenton reagent in step two is 0.01% - 0.1% (wt), and the volume of hydrogen peroxide is 5 - 15 mL.
[0068] By strictly controlling the content of iron ions in the Fenton reagent and the volume of hydrogen peroxide, the performance of the prepared product is made more excellent.
[0069] Among them, the temperature of the hydrothermal reaction in step three is set at 140 - 200 °C, and the time is set at 6 - 12 h.
[0070] By controlling the hydrothermal reaction temperature and time, a graphene electrode material with higher conductivity is prepared, improving the stability of the electrode material during the electrochemical cycling process.
[0071] Among them, after the hydrothermal reaction of the mixed solution on the surface of the conductive substrate in step three, the obtained reaction product is successively subjected to washing, drying, and cooling treatments.
[0072] By washing and drying the reaction product, the morphology and structure of the reaction product can be controlled. Washing can remove excess liquid and unfixed substances, while drying can make the reaction product form a stable solid form, which is beneficial for subsequent processing and application.
[0073] Among them, the reaction product is washed with deionized water or ethanol, and after washing, the reaction product is dried by vacuum drying, with the drying temperature set at 40 - 70 °C and the drying time at 6 - 12 h.
[0074] By controlling the drying temperature, it is possible to avoid incomplete drying of the reaction product due to too low a temperature, and at the same time avoid structural changes or performance loss of the reaction product due to too high a temperature. At the same time, the control of the drying time ensures that the product can be fully dried.
[0075] An application of a binder-free graphene electrode material, where the graphene material is used as a working electrode in a supercapacitor.
[0076] The prepared graphene material has a high specific capacitance per unit area and good electrochemical performance. When used as a working electrode in supercapacitors, it has excellent application prospects.
[0077] Example 3
[0078] As Figure 3 、 Figure 4 、 Figure 5 、 Figure 10 and Figure 11 shown, an embodiment of the present invention provides a binder-free graphene electrode material, which includes a conductive substrate and a graphene material. The graphene material is loaded on the conductive substrate through a green one-step hydrothermal reaction.
[0079] Graphene has an extremely high electron mobility and excellent electrical conductivity. Loading it on a conductive substrate can further enhance the electrical conductivity of the entire system.
[0080] Among them, the conductive substrate is one of nickel foam, carbon cloth or carbon paper.
[0081] By selecting nickel foam, carbon cloth or carbon paper as the conductive substrate, the electrochemical performance of the composite material can be significantly improved after combining with graphene.
[0082] A preparation method of a binder-free graphene electrode material includes the following steps:
[0083] Step 1: First, dissolve graphene ink in deionized water for dilution. Dilute the ink by 8 times, stir evenly and then sonicate. The stirring time is 0.5 hours and the sonication time is 0.5 hours to obtain a uniformly dispersed dilution.
[0084] Step 2: Select ferric chloride as the iron source in the Fenton reagent, and add the Fenton reagent to the dilution obtained in Step 1 to obtain a mixture.
[0085] Step 3: Prepare the pretreated nickel foam as the conductive substrate in advance and set it aside. Then vertically fix the conductive substrate at the bottom of a polytetrafluoroethylene-lined reaction kettle. Next, pour the mixture obtained in Step 2 into the reaction kettle, and carry out a hydrothermal reaction of the mixture on the surface of the conductive substrate in a constant temperature hydrothermal oven. The temperature of the hydrothermal reaction is 180 °C and the hydrothermal reaction time is 8 h. After the hydrothermal reaction, first wash the obtained reaction product with deionized water and anhydrous ethanol in sequence. After washing, dry the reaction product by vacuum drying. The drying temperature is 60 °C and the drying time is 6 h. After drying, cool the reaction product to room temperature to obtain the binder-free graphene electrode material;
[0086] The pretreatment steps of nickel foam are as follows: First, cut the nickel foam into nickel foam blocks with a size of 1×1×2 cm. Then, ultrasonically clean the nickel foam blocks with anhydrous ethanol and deionized water in sequence. The cleaning time is 15 min. After cleaning, dry them in a vacuum oven at a drying temperature of 60 °C for 6 h to obtain the pretreated nickel foam.
[0087] Use the prepared graphene electrode as the working electrode, a platinum sheet as the counter electrode, Hg / HgO as the reference electrode, and 6 mol / L KOH solution as the electrolyte to form a three-electrode system. Use a Shanghai Chenhua electrochemical workstation (CHI 760E) to perform cyclic voltammetry tests and constant current charge-discharge tests on the prepared graphene electrode material. The obtained cyclic voltammogram is as shown in the accompanying drawings of the specification Figure 10 as shown, and the constant current charge-discharge curve is as shown in the accompanying drawings of the specification Figure 11 as shown. It is calculated that when the current density is 2 mA / cm 2 , the specific area capacitance of the obtained electrode material is 2149.74 mF / cm 2 . By dissolving the graphene ink in deionized water for dilution and through stirring and ultrasonic treatment, a uniformly dispersed graphene diluent can be obtained, improving the dispersibility of graphene in the solution and providing a uniform reaction environment for subsequent reactions. Finally, the prepared self-supporting graphene electrode material has excellent conductivity and does not use strong acids, playing a role in protecting the environment and having broad application prospects in batteries and supercapacitors.
[0088] Among them, in step two, the Fenton reagent source is selected from one or more of ferric chloride, ferric sulfate, and ferric nitrate.
[0089] By using ferric chloride, ferric sulfate, and ferric nitrate as the Fenton reagent, the preparation cost is reduced, making the product more economical and practical.
[0090] Among them, in step two, the content of iron ions in the Fenton reagent is 0.01% - 0.1% (wt), and the volume of hydrogen peroxide is 5 - 15 mL.
[0091] By strictly controlling the content of iron ions in the Fenton reagent and the volume of hydrogen peroxide, the performance of the prepared product is made more excellent.
[0092] Among them, in step three, the temperature of the hydrothermal reaction is set to 140 - 200 °C, and the time is set to 6 - 12 h.
[0093] By controlling the hydrothermal reaction temperature and time, a graphene electrode material with higher conductivity is prepared, improving the stability of the electrode material during the electrochemical cycle.
[0094] Among them, after the hydrothermal reaction of the mixed solution on the surface of the conductive substrate in Step 3, the obtained reaction product is successively washed, dried, and cooled.
[0095] By washing and drying the reaction product, the morphology and structure of the reaction product can be controlled. Washing can remove excess liquid and unfixed substances, while drying can make the reaction product form a stable solid form, which is beneficial to subsequent processing and application.
[0096] Among them, the reaction product is washed with deionized water or ethanol, and after washing, the reaction product is dried by vacuum drying. The drying temperature is set at 40-70 °C, and the drying time is 6-12 h.
[0097] By controlling the drying temperature, it is possible to avoid incomplete drying of the reaction product due to too low a temperature, and at the same time avoid structural changes or performance loss of the reaction product due to too high a temperature. At the same time, the control of the drying time ensures that the product can be fully dried.
[0098] An application of a binder-free graphene electrode material, where the graphene material is used as a working electrode in a supercapacitor.
[0099] The prepared graphene material has a high specific capacitance per unit area and good electrochemical performance. As a working electrode in a supercapacitor, it has good application prospects.
[0100] It should be noted that in this article, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the term "comprising", "including" or any other variation thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article or device.
[0101] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A binder-free graphene electrode material, comprising a conductive substrate and a graphene material, characterized in that: The graphene material is loaded on a conductive substrate through a green one-step hydrothermal reaction.
2. The binder-free graphene electrode material according to claim 1, characterized in that: The conductive substrate is one of foamed nickel, carbon cloth or carbon paper.
3. A method for preparing a binder-free graphene electrode material, characterized in that: The following steps are involved: Step 1: First, dissolve the graphene ink in deionized water, dilute it, stir it evenly and perform ultrasound to obtain a uniformly dispersed dilution solution; Step 2: adding Fenton's reagent to the dilution obtained in step 1 to obtain a mixed solution; Step 3: Place the pre-prepared conductive substrate into the mixed solution obtained in step 2 to carry out a hydrothermal reaction, and then wash and dry to obtain a self-supporting graphene electrode material.
4. The method for preparing a binder-free graphene electrode material according to claim 3, characterized in that: The Fenton reagent source in step 2 is selected from one or more of ferric chloride, ferric sulfate and ferric nitrate.
5. The method for preparing a binder-free graphene electrode material according to claim 3, characterized in that: The content of iron ions in the Fenton reagent in step 2 is 0.01% to 0.1% (wt), and the volume of hydrogen peroxide is 5 to 15 mL.
6. The method for preparing a binder-free graphene electrode material according to claim 3, characterized in that: The temperature of the hydrothermal reaction in step 3 is set to 140-200° C., and the time is set to 6-12 hours.
7. The method for preparing a binder-free graphene electrode material according to claim 3, characterized in that: In step 3, the reaction product obtained after the mixed solution undergoes hydrothermal reaction on the surface of the conductive substrate is washed, dried and cooled in sequence.
8. The method for preparing a binder-free graphene electrode material according to claim 7, characterized in that: The reaction product is washed with deionized water or ethanol, and after washing, the reaction product is dried in a vacuum drying manner, with the drying temperature being set at 40 to 70° C. and the drying time being set at 6 to 12 hours.
9. An application of a binder-free graphene electrode material, characterized in that: The graphene material is used as a working electrode in a supercapacitor.